Associated plants and distribution of the orchid bee genus Eulaema (Apidae: Bombinae: Euglossini) in Venezuela - González, Jorge (Boletín del Centro de Investigaciones Biológicas)
Orchid bees (Eulaema spp.) were observed and collected with chemical baits in 14 of the 23 States of Venezuela, from 1989 to 1998. Ten species are present, and Eulaema meriana flavescens, E. nigrita and E. bombiformis are the most abundant. Nine species bore orchid pollinaria or visited orchids, but bees also visited plant species other than orchids (mainly Caesalpinaceae). Certain orchids have probably evolved in response to euglossine pollination pressure, but there is no clear indication that reciprocal evolution has taken place.